PENDEKATAN INQUIRY-BASED LEARNING BERTEMA SUSTAINABLE DEVELOPMENT GOALS PADA PEMBELAJARAN STATISTIKA KELAS X - Ahmad Faiz Chudori; Riki Suliana; Moh. Khafid Irsyadi (STKIP Subang, 2026)
This study aims to analyze the implementation of the Inquiry-Based Learning approach, focusing on the theme of the Sustainable Development Goals, in the statistics curriculum for 10th-grade. This study employed a qualitative approach using the case study method, involving 25 students and 1 teacher from Class selected through purposive sampling specifically, three students representing the high (ST), moderate (SS), and low (SR) ability categories. Data were collected through analysis of Student Worksheets (LKPD), interviews, and documentation. Data validity was ensured through instrument validation by experts (expert judgment), source triangulation, and methodological triangulation. Data analysis utilized the Miles et al. (2014) v-model, which includes data reduction, data presentation, and drawing conclusions. The research results indicate that the Inquiry-Based Learning approach with the theme of the Sustainable Development Goals (SDGs) can help students build an understanding of statistical concepts through the stages of problem orientation, formulating questions, collecting and processing data, analyzing data, and drawing conclusions. The findings revealed differences in the level of understanding across each category of student ability. High-ability students were able to understand the concepts more deeply and connect the results of their analysis to the context of the SDGs, whereas students with moderate and low abilities still required guidance during the data analysis and interpretation stages. The use of SDG themes makes learning more contextual and increases student engagement; however, implementing this approach requires effective classroom management, teacher guidance, and good time management to ensure that each stage of Inquiry-Based Learning can proceed optimally.